β-Catenin Is a Positive Regulator of Estrogen Receptor-α Function in Breast Cancer Cells - Gupta, Nibedita (Molecular Diversity Preservation International (MDPI), 2011)
Estrogen receptor-alpha (ERα) is a key factor in the development of breast cancer in humans. The expression and activity of ERα is regulated by a multitude of intracellular and extracellular signals. Here we show a cross-talk between β-catenin and ERα in human breast cancer cells. Knockdown of β-catenin by RNAi resulted in significant reduction of ERα mRNA and/or protein levels in MCF-7, T-47D, and BT-474 breast cancer cells and in significant reduction of estradiol-induced expression of the ERα target genes pS2 and GREB1. In addition β-catenin silencing resulted in significant decrease of growth of MCF-7 cells both in the absence and presence of estradiol. β-catenin and ERα could not be co-immunoprecipitated by ERα antibodies from lysates of E2-treated or untreated cells suggesting lack of direct physical interaction. It is concluded that β-catenin is a positive regulator of ERα mRNA and protein expression.